Modification of logical reasoning through an informal gamification platform - Holguin Alvarez, Jhon Alexander (2020)
Informal Gamification based on video games turns out to be attractive due to its playful presentation, its motivational resources, and open access. This is important for the benefit of cognitive constructs such as logical reasoning, in the area of mathematics. Through this research, we implemented an experimental program based on the inclusion of the Plants vs Zombies video game as a cognitive modifier of reasoning. We developed the Gamification project through a pre-experimental design for six months. The sample consisted of 96 Basic Education students (M = 6.56 years of age; SD = 0.3). The pre-calculation test allowed us to contrast results between the pretest and posttest measurements. We obtained effective results in the dimensions of seriation, cardinality and cognitive conservation. The effects were much more decisive in conservation. These results allowed obtaining that the complexity of this game allowed to reduce the cognitive reload in the mathematical operations, as well as to increase the sustained attention in the development of logical reasoning tasks, and to achieve greater fluency in the operational calculation.